Home-based exercise in patients with refractory fatigue associated with primary biliary cholangitis: a protocol for the EXerCise Intervention in cholesTatic LivEr Disease (EXCITED) feasibility trial. Issue 1 (11th March 2021) - Freer, Alice; Williams, Felicity; Durman, Simon; Hayden, Jennifer; Trivedi, Palak J; Armstrong, Matthew J
Abstract : Introduction: Fatigue is the most commonly reported symptom of the liver disease primary biliary cholangitis (PBC). It affects 40%–80% of patients, has no effective treatment and is associated with heightened mortality risk. The pathogenesis is unknown, but muscle bioenergetic abnormalities have been proposed to contribute. Directly observed exercise has been shown to attenuate symptoms in small groups; however, due to the rare nature of the disease, home-based interventions need to be evaluated for feasibility, safety and efficacy. Methods and analysis: This is a phase 1/pilot, single-arm, open-label clinical trial evaluating a novel home-based exercise programme in patients with PBC with severe fatigue. Forty patients with moderate-severe fatigue (PBC40 fatigue domain score >33; other causes of fatigue excluded) will be selected using a convenience sampling method. A 12-week home-based exercise programme, consisting of individualised resistance, aerobic exercises and telephone health calls (first 6 weeks only), will be delivered. Measures of fatigue (PBC40 fatigue domain; fatigue impact scale), quality of life, sleep (Epworth Sleep Score), physical activity, anxiety and depression, aerobic exercise capacity (incremental shuttle walk test; Duke Activity Status Index) and functional capacity (short physical performance battery) will be assessed at baseline and at 6 and 12 weeks following the intervention. Ethics and dissemination: The protocol is approved by the National Research Ethics Service Committee London (IRAS 253115). Recruitment commenced in April 2019 and ended in March 2020. Participant follow-up is due to finish by December 2020. Findings will be disseminated through peer-reviewed publication, conference presentation and social media. Trial registration number: NCT04265235 .